If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + x + -5 = 12 Reorder the terms: 8 + -5 + x = 12 Combine like terms: 8 + -5 = 3 3 + x = 12 Solving 3 + x = 12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + x = 12 + -3 Combine like terms: 3 + -3 = 0 0 + x = 12 + -3 x = 12 + -3 Combine like terms: 12 + -3 = 9 x = 9 Simplifying x = 9
| .5(x+4)+3=2x(.22+.75) | | -2(3x-4)=8 | | x+3x+5x+7x+9x+11x+13x+15x+17x=162 | | 7x+y=23 | | (x-3)-(2x+5)=2x-7-3x | | m(x)=-5x^3+8x+4 | | X/4+4=19 | | m-99=-9 | | 8=8v-16 | | x/20=52.5/75 | | x/75=27/100 | | J/5+1=19 | | 14x+2=2x+142 | | 3/2y=-1/2x+1 | | (4^16)1/2 | | 3/2y=-1/2+1 | | 3(2x-10)=30 | | 4(3y-5)=-36 | | 3x-15y-30=0 | | 0.8+x=0.7+2-0.1 | | -y=-2/3x+5 | | -8(3x+4)+6x=4(x-8)+4x | | 0=-16t^2+10t+50 | | -36+20= | | -6-24y=8x | | -6-24=8x | | 2g+g-7=1+3g | | 4x+6x+2+8=5x+5+4x | | -(6y+1)=-4(-10-4y) | | 2(12-8x)=2+14t | | 3y=-3x-1 | | 0.2k-4.21-0.8k=2(-k+0.1) |